OCCURRENCE OF INFECTIOUS AND PARASITIC DISEASES IN ASSOCIATION WITH THE OUTDOOR HABITS OF HOUSEHOLD DOGS AND CATS A CASE-CONTROL STUDY - PEREIRA, N. W. B.; CHICONINI, M.; LEONEL, J. A. F.; BENASSI, J. C.; RUIZ, V. L. A.; KEID, L. B.; FERREIRA, H. L.; SOARES, R. M.; OLIVEIRA, T. M. F. S. (Ars Veterinaria, 2018)
Many owners believe to act in their pets’ best interest by allowing them to go outside, with or without supervision. However, outdoor exposure greatly increases the risk of disease and accidents. In this study, we evaluated the association between infectious and parasitic diseases and the outdoor habits of pet dogs and cats. Epidemiological data were obtained from the records of dogs and cats treated at the Teaching Clinic and Hospital Unit of Veterinary Medicine in the city of Pirassununga, state of São Paulo, Brazil. Pets with any form of infection were included in the case study group, and pets with no infectious or parasitic diseases were used as controls. Animals were further divided according to their habits into indoor animals, indoor animals taken for walks, and outdoor animals. The odds ratio of having a disease was calculated from the comparisons among these groups using the MedCalc Statistical Software. We found an increased risk for the occurrence of infectious or parasitic diseases in outdoor dogs and cats when compared to indoor animals (OR of 4.735) and to those taken for walks (OR of 2.303). In light of our results, we suggest that awareness campaigns should also focus on the benefits of keeping pets indoors.